50 Years of phytochemistry research : Volume 43 (Recent Advances in Phytochemistry, 2013)
The Phytochemical Society of North America (PSNA) is a nonprofit scientific organization with membership open to those interested in plant biochemistry, phytochemistry, and the role of plant substances in related disciplines. The PSNA exists to encourage and stimulate research in the chemistry and biochemistry of plant constituents, their effects upon plant and animal physiology and pathology, and their industrial importance and utilization. Annual meetings featuring symposium topics of current general interest and contributed papers by conference participants are held throughout Canada, the United States, and Mexico. PSNA meetings provide participants with exposure to cutting-edge research presented by prominent international scientists, but remain intimate enough to allow interaction and collegiality. Recent meetings were previously held jointly with the American Society of Pharmacognasy in St. Pete Beach, FL USA (2010), or held at Towson University, Maryland, USA (2009) and the 50th Anniversary Meeting of the PSNA at the Fairmont Orchid, Waikaloa, Hawai'i USA (2011). Information about the PSNA, can be found at www.psna-online.org.